Neuromodulation in the treatment of symptoms of spinal cord injury - Niemirski, Dominik; Machowiec, Piotr; Komisarczuk, Mateusz; Maksymowicz, Marcela; Leszczyk, Patryk; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2020)
Introduction and purpose: Spinal cord injury may be associated with loss of motor and sensory functions, autonomic system functions and chronic pain. The development of technology has enabled the emergence of invasive and non-invasive methods of electrical and magnetic stimulation of the nervous system, which show a growing potential in the treatment of these symptoms in human and animal studies. The purpose of the study is a presentation of the most current studies about the selected methods of neuromodulation of the nervous system in the treatment of symptoms of spinal cord injury. Description of the state of knowledge: Neuromodulatory methods improve the functioning of patients affected by spinal cord injury. Studies on epidural stimulation of the spinal cord, transcranial magnetic stimulation, transcranial direct current stimulation transcutaneous spinal cord, and use of neuromodulation methods in combination with brain-machine interfaces stimulation show a reduction of chronic pain resistant to pharmacotherapy, improvement of motor limb function, respiratory function and bladder function. However, there are few large randomized studies with higher evidence strength. Conclusions: Neuromodulation is effective in the treatment of symptoms of spinal cord injury. Promising results should lead to further research to increase the strength of evidence for the effectiveness of these therapies, improve technology and a deeper understanding of the mechanisms behind their effectiveness.